Ideologieübergreifende Radikalisierung als sozialstrukturelles Problem. Überlegungen zur Trennschärfe von Begriffen und interdisziplinären Aufgaben der Radikalisierungsforschung - Bärbel Bongartz (IUBH Internationale Hochschule, 2020)
– It is difficult to reach scientific agreement on concepts and explanations of the phenomenon of terrorism. One reason may be the diversity of terrorist acts, another is certainly the imprecise and careless use of the term. The struggle for a conceptual framing of the phenomenon of terrorism and a precise definition remains; some terrorism researchers, such as Christopher Daase, even argue that the search for the semantic core of terrorism should be abandoned (Daase, 2011, p. 29). This must not lead to abandoning research into the nature of terrorism. Rather, it is time to expand the phenomenon conceptually, in order to then specify it again in its diversity. A first theoretical appeal is to focus less on the concept of terrorism and more on facets of politically motivated crime, including hate crimes.
Keywords: 300; Ideologieübergreifende Radikalisierung; theoretische Ansätze der Radikalisierungsforschung; interdisziplinäre Zusammenarbeit; Terrorismus; Hassverbrechen